If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+27=2(x+5)-10
We move all terms to the left:
5x+27-(2(x+5)-10)=0
We calculate terms in parentheses: -(2(x+5)-10), so:We add all the numbers together, and all the variables
2(x+5)-10
We multiply parentheses
2x+10-10
We add all the numbers together, and all the variables
2x
Back to the equation:
-(2x)
3x+27=0
We move all terms containing x to the left, all other terms to the right
3x=-27
x=-27/3
x=-9
| 26=2(3x+4) | | 2x-7=2(2x-4)+5 | | -2x-173=124-11x | | 42=2(4x+5) | | 5x-34=2(5x+3) | | 16=4(2x-4) | | 13x–2(X-4)=8x+1 | | 3(5x-3)-1=-4x-29 | | -201-2x=10x+75 | | 3(x-4)-5=2x-26 | | (x-4)-5=2x-26 | | -14x-63=-9x+32 | | -95=6x | | 2x+19=49-3x | | 4=3h-h+2+10 | | 6x-88=13x+171 | | x=4/2x-4 | | 8x+29=−21+3x | | 16=7t-9 | | 24+24x=150+10x | | X(13-2x)=15 | | -25+2x=43+4x | | x+9=7x+9+6x | | 122y=4 | | 2u-5/3=-1/5u-4/5 | | 2x²5x18=0 | | -9x-24=18-7x | | -11x-90=165+6x | | 3x-3+7=4x+2-3x+6 | | 2x-3=4x–7 | | -x-121=-7x+41 | | -83-x=62-6x |